The Effect of Molasses Concentration on the Growth of Yeast Saccharomyces Cereviceae in Making Single Cell Proteins the Effect of the concentrate on of Waste Molasses on the Growth of Yeast Saccharomyces Cereviceae in the Making of Single Cell Proteins - Bahtiar, Virdhalya Kartika; Patang, Patang; Indrayani, Indrayani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of the research was to determine the optimal molasses concentration for the growth of Saccharomyces Cereviciae yeast and the protein content of Saccharomyces cerevisiae yeast in making PST. This research used an experimental method with a quantitative approach and used a Completely Randomized Design (CRD) with 5 treatments and 3 replications. The concentrations in this study were 10%, 15%, 20%, 25% molasses and control. The results obtained showed that the protein levels obtained ranged from 13-47%. Apart from that, the highest specific growth rate (SGR) and protein productivity were found in the M1 treatment with 10% molasses.